MAJALAH SUBMATERI PEMANFAATAN KEANEKARAGAMAN HAYATI INDONESIA BERDASARKAN INVENTARISASI TUMBUHAN SEBAGAI BAHAN KERAJINAN TANGAN - Oktavia Oktavia; Syamswisna Syamswisna; Reni Marlina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research aimed to determine the types of plants that are used as handicrafts by the people of Hlibuei Village, Bengkayang Regency, from the results of the inventory and to find out the results of the feasibility of the magazine as a learning media in the sub material of Biodiversity Utilization for Grade X of Senior High School. The method used in this type of qualitative research was descriptive with sampling techniques using purposive sampling. Data collection techniques used triangulation which was a combination of interview, observation and documentation. From the research results, there were 23 types of plants that were used as handicraft materials which included 9 families. The results of the research are then implemented in the form of magazine media. The media of the magazine was tested for eligibility by two Biology Education lecturers from FKIP Untan and 5 Biology teachers class X of Senior High School in three schools namely SMAN 2 Siding, SMAN 1 Jagoi Babang and SMAN 1 Seluas. Based on the validator's assessment, the magazine was suitable to be used as a learning media in the sub material of Indonesian biodiversity utilization, with a CVR value of 0.99 in accordance with the minimum CVR value of Lawshe for 5 validators, namely 0.99. Keywords: Inventory, Magazine, Plants as Handicrafts